2017
DOI: 10.7448/ias.20.1.21437
|View full text |Cite
|
Sign up to set email alerts
|

High self‐reported non‐adherence to antiretroviral therapy amongst adolescents living with HIV in Malawi: barriers and associated factors

Abstract: Introduction: Globally adolescents and young adults account for more than 40% of new HIV infections, and HIV-related deaths amongst adolescents increased by 50% from 2005 to 2012. Adherence to antiretroviral therapy (ART) is critical to control viral replication and preserve health; however, there is a paucity of research on adherence amongst the growing population of adolescents living with HIV/AIDS (ALHIV) in Southern Africa. We examined levels of self-reported ART adherence, barriers to adherence, and facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
131
2
7

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(154 citation statements)
references
References 47 publications
14
131
2
7
Order By: Relevance
“…This result was also found in a study conducted in Zambia among 15 -19-years old adolescents [20]. However, other studies have shown no significant difference between girls and boys [21]. This difference in the rate of non-adherence to ART between girls and boys HIV infected varies from one region to another.…”
Section: Factors Associated With Non-adherence To Artsupporting
confidence: 75%
“…This result was also found in a study conducted in Zambia among 15 -19-years old adolescents [20]. However, other studies have shown no significant difference between girls and boys [21]. This difference in the rate of non-adherence to ART between girls and boys HIV infected varies from one region to another.…”
Section: Factors Associated With Non-adherence To Artsupporting
confidence: 75%
“…Médecins sans Frontières has also piloted a Youth Clubs program in Cape Town, including a structured interactive activity‐based session rooted in peer support that has been endorsed in the South African national adherence policy. Few interventions, however, have been described in the peer‐reviewed literature and evaluations have not looked at retention in care as an outcome . This is one of the first studies to date to look at the impact of an adolescent focused differentiated model of care on ART retention.…”
Section: Discussionmentioning
confidence: 99%
“…Further qualitative research in particular around the barriers associated with retention in care, non‐adherence, the effect on Teen Club programming on these barriers, and disentangling the individual factors that may prompt ALHIV to choose standard of care versus Teen Club, would be valuable in evidence‐informed program modification. A recent cross sectional study of a representative sample of ALHIV in the ZCH clinic and another large tertiary referral clinic in Malawi, looked at barriers and associated factors to self‐reported non‐adherence and found the most commonly reported barriers to adherence included forgetting (>90%), travel from home (14%), and “busy doing other things” (11%). Drinking alcohol in the past month, witnessing or experiencing violence in the home in the past year, and poor treatment self‐efficacy were each found to be independently associated with missing ART in the past week.…”
Section: Discussionmentioning
confidence: 99%
“…Public access to ART within hyper-endemic and resource-constrained settings has allowed for a more sustained focus on the practicable and experiential challenges of adolescent ART adherence within an array of settings (Merten et al, 2010;Sahay, Reddy, & Dhayarkar, 2011). A number of recent studies on adherence have sought to confront challenges of representativeness through locating research within multiple sites, providing potential for comparison across different locations and adolescent populations (Bernays et al, 2017;Kim et al, 2017;Nabukeera-Barungi et al, 2015). As an adjunct to research focusing on the clinical efficacy of ART, studies on ART adherence have included components on the socio-behavioural factors of adherence.…”
Section: Expanding Contexts Of Art Adherencementioning
confidence: 99%